On the non-disabled perceptions of four common mobility devices in Norway: A comparative study based on semantic differentials - Boiani, Josieli Aparecida Marques [UNESP]; Barili, Sara Raquel Martins [UNESP]; Medola, Fausto Orsi [UNESP]; Sandnes, Frode Eika (SAGE Publications, 2019)
BACKGROUND: Mobility devices such as walkers and wheelchairs are often associated with certain stigma. Such devices must be designed with the goal of reducing stigma to decrease the abandonment-rate. Yet there is little empirical evidence on how mobility devices are perceived. OBJECTIVE: This study set out to explore how (N= 40) non-disabled individuals perceived four common mobility devices including a traditional walker, rollator, manual wheelchair and a powered wheelchair. METHODS: A questionnaire based on semantic differential scales was designed. RESULTS: The results show that the more elaborate devices are perceived as more aesthetical and lighter, yet more unsafe and impractical. Moreover, respondents familiar with mobility devices through family and friends gave more biased negative responses in terms of device characteristics compared to non-experienced respondents. Next, non-experienced respondents perceived the manual wheelchair to be more stigmatizing compared to experienced respondents. CONCLUSIONS: The findings evidence that different designs of products in the same category can evoke different perceptions of non-users regarding practical, aesthetical and symbolic aspects. Insight into how different design characteristics are associated with perceptions of non-users may contribute to the comprehension of assistive technology stigma and may support design decisions that minimize negative judgments and emphasize positive perceptions.
Keywords: aesthetics; Assistive technology; cultural factors; operations; perceptions; stigma; walkers; weight; wheelchairs